STRENGTHENING CIVIC EDUCATION ON THE NATIONALISM ATTITUDE OF INDONESIAN MIGRANT WORKERS' CHILDREN IN SELANGOR MALAYSIA - Edwin Dwi Hartanto; Ardhana Januar Mahardhani; Hadi Cahyono; Zamawi Chaniago (Lembaga Penelitian Mahasiswa Penalaran UNM, 2023)
The objective of this research is identify and understand the impact of strengthening civic education on the nationalism attitudes of children of Indonesian migrant workers in Selangor, Malaysia, and provide guidelines to strengthen their nationalism identity. This research is a descriptive study using qualitative methods and participatory and collaborative approaches. Data were collected through observation, interviews, data analysis and documentation of 4th, 5th and 6th grade students at Hulu Langat Guidance Center. The data analysis technique used is Qualitative data analysis technique including Data Reduction, Data Presentation and Conclusion Drawing or Verification. The results showed that the strengthening of comprehensive civic education had a significant effect on the knowledge and nationalism attitudes of children of migrant workers, including the Indonesian president, the basis of the state and the application of the Pancasila precepts in everyday life. So it is concluded that strengthening comprehensive civic education has a very important role in improving the nationalism attitudes of children of migrant workers